Images of Korea III [videorecording] ([S.l.] The Foundation)
Presents Korean's Pansori Salpuri, painting, temples and shrines and their cultural treasures.
VHS.
Keywords: Korea Foundation; Link Production; Music -- Korea; Dance -- Korea; Paintings -- Korea; Rites and ceremonies -- Korea; 0Korea -- Social life and customs; Temples -- Korea; Shrines -- Korea; Korea -- Antiquities; Korea -- Description and travel